Interactions between inhibitors of dihydrofolate reductase. - Bowden, K (1989)
The binding of substrates and inhibitors to dihydrofolate reductase was studied by steady-state kinetics and high-field 1H-n.m.r. spectroscopy. A series of 5-substituted 2,4-diaminopyrimidines were examined and were found to be 'tightly binding' inhibitors of the enzyme (Ki less than 10(-9) M). Studies on the binding of 4-substituted benzenesulphonamides and benzenesulphonic acids also established the existence of a 'sulphonamide-binding site' on the enzyme. Subsequent n.m.r. experiments showed that there are two binding sites for the sulphonamides on the enzyme, one of which overlaps the coenzyme (NADPH) adenine-ring-binding site. An examination of the pH-dependence of the binding of sulphonamides to the enzyme indicated the influence of an ionizable group on the enzyme that was not directly involved in the sulphonamide binding. The change in pKa value from 6.7 to 7.2 observed on sulphonamide binding suggests the involvement of a histidine residue, which could be histidine-28.